Design and performance analysis of efficient hybrid mode multi-ported memory modules on FPGA platform - Druva Kumar Siddaraju; Roopa Munibyrappa (Institute of Advanced Engineering and Science, 2022)
The multi-ported memories (MPMs) are essential and are part of the parallel computing system for high-performance features. The MPMs are commonly used in most processors and advanced system-on-chip (SoC) for faster computation and high-speed processing. In this manuscript, efficient MPMs are designed using the integration of hierarchical bank division with xor (HBDX) and bank division with remap table (BDRT) approaches. The BDRT approach is configured using remap table with a hash write controlling mechanism to avoid write conflicts. The different multiple read ports are designed using BDX, and HBDX approaches are discussed in detail. The results of 2W4R and 3W4R memory modules are analyzed in detail concerning chip area, operating frequency (MHz), block random access memories (BRAMs), and throughput (Gbps) for different memory depths on virtex-7 field programmable gate array (FPGA). The 2W4R utilizes 2.27% slices, operates at 268 MHz frequency by consuming 64 BRAMs for 16K memory depth. Similarly, the 3W4R uses 2.28% slices, operates at 250 MHz frequency by consuming 96 BRAMs for 16K Memory depth. The proposed designs are compared with existing MPM approaches with better chip utilization (Slices), frequency, and BRAMs on the same FPGA device.